A Comparison between the i-gel® and air-Q® Supraglottic Airway Devices Used for the Patients Undergoing General Anesthesia with Muscle Relaxation. (18th November 2018) - Massoudi, Nilofar; Fathi, Mohammad; Nooraei, Navid; Salehi, Alireza
Abstract : Objectives . The aim of the present study was to compare two supraglottic airway (SGA) devices (i.e., the i-gel® © Intersurgical Ltd and air-Q® (Reusable) Cookgas company) in terms of the insertion time, amount of leak during ventilation with maximum positive pressure, and postoperative complications in patients referring to Modarres Hospital in Tehran. Method. The present double-blind clinical trial was performed on 60 patients undergoing elective surgeries that required general anesthesia with muscle relaxation. Patients were randomly assigned to either i-gel® ( n = 30) or Air-Q® ( n = 30) groups. Results. The mean age, body mass index, duration of surgery, duration of anesthesia, and gender ratio were not significantly different between the two groups. Mean ± SD values of the SGA devices' insertion time (in seconds) in the air-Q® and i-gel® groups were 4.87 ± 1.6 and 6.80 ± 1.2, respectively (P < 0.001). The mean OLP in the Air-Q® group was significantly higher than that of the i-gel® group (35.9 ± 9.6 versus 24.8 ± 3.7, p < 0.001). The frequency of complications occurred after the supraglottic airway insertion was higher in the i-gel® group. However, only in terms of sore throat, the difference between the two groups was statistically significant: 6 (20%) had sore throat (P = 0.024) in the i-gel groups, but in in the Air-Q® groups no one had this side effect after surgery. Conclusion. It was concluded that the Air-Q® supraglottic airway was placed faster and easier with fewer complications than the i-gel in general anesthesia with muscle relaxation. The frequency of the occurrence of all three complications, cough, sore throat, and blood, on the cuff (6 (20%) was higher in the i-gel group than that in the air-Q® group (cough3 (10%), sore throat 0 (0%), and blood on the cuff 3 (10%) (P < 0.05).